2016
DOI: 10.1007/s11425-016-0301-5
|View full text |Cite
|
Sign up to set email alerts
|

A note on semidefinite programming relaxations for polynomial optimization over a single sphere

Abstract: We study two instances of polynomial optimization problem over a single sphere. The first problem is to compute the best rank-1 tensor approximation. We show the equivalence between two recent semidefinite relaxations methods. The other one arises from Bose-Einstein condensates (BEC), whose objective function is a summation of a probably nonconvex quadratic function and a quartic term. These two polynomial optimization problems are closely connected since the BEC problem can be viewed as a structured fourth-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Though general-purpose polynomial solvers based on the sum-of-squares framework [28,29,30,31,32,27,36] can be utilized (as we did in the subsection 4.2), more efficient and scalable methods (e.g. projected gradient method [26], semidefinite programming relaxations [20,21,23]), specifically tailored to the structure of (1.3), may be anticipated. This is definitely a promising future research direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though general-purpose polynomial solvers based on the sum-of-squares framework [28,29,30,31,32,27,36] can be utilized (as we did in the subsection 4.2), more efficient and scalable methods (e.g. projected gradient method [26], semidefinite programming relaxations [20,21,23]), specifically tailored to the structure of (1.3), may be anticipated. This is definitely a promising future research direction.…”
Section: Discussionmentioning
confidence: 99%
“…Review on SROAwRD. Algorithm 1 is intensively studied in the tensor community, though most papers [14,8,15,16,17,18,12,13,19,20,21,22,7,23,24] focus on the numerical aspects of how to solve the best tensor rank-one approximation (1.2). Regarding theoretical guarantees for the symmetric and orthogonal decomposition, Zhang and Golub [8] first prove that SROAwRD outputs the exact symmetric and orthogonal decomposition if the input tensor is symmetric and orthogonally decomposable:…”
Section: Notationmentioning
confidence: 99%
“…Despite recent progress on the geometric properties of nonconvex minimization problems and due to the complex interaction of the quadratic and quartic terms, the landscape of (1.1) is still elusive. We further note that in [40], Hu et al have shown that the minimization problem (1.1) can be interpreted as a special instance of the partition problem and thus, it is generally NP-hard to solve (1.1).…”
Section: Introductionmentioning
confidence: 93%
“…The problem above can be also regarded as the best rank-1 tensor approximation of a fourth-order tensor F [39], with…”
mentioning
confidence: 99%